Urgensi Perubahan Kelima Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 Sebagai Upaya Penguatan Independensi Kelembagaan Mahkamah Konstitusi - Gusman, Delfina (Nagari Law Review, 2025)
Inevitably, the same problem, namely the infertility of the judicial institution, is also one of the problems that occurs in Indonesia. One of the processes in changing the 1945 Constitution of the Republic of Indonesia is to reconstruct the judicial power institution. As one of the judicial authorities, the Constitutional Court has the independent authority to administer justice to uphold law and justice. In carrying out its adjudicating function, the Constitutional Court has nine constitutional judges appointed by the President, with three nominated by the Supreme Court, three by the House of Representatives, and three by the President. The Constitutional Court is not immune to controversial issues that intersect with its independence. The regression of democracy in Indonesia is increasingly apparent when institutions, such as the Constitutional Court, are caught up in practical politics. Issues arise regarding the weakness of the Constitutional Court system regulated in the 1945 Constitution of the Republic of Indonesia, particularly the system for filling constitutional judge positions, which impacts the Constitutional Court's independence.Are controversial cases in the Constitutional Court that overlap with independence caused by the weakness of the system related to the Constitutional Court as regulated in the 1945 Constitution of the Republic of Indonesia? The research method used is normative juridical. The results of the research, filling the position of constitutional judge through the House of Representatives, the Supreme Court and the President as mandated by Article 24C paragraph (3) of the 1945 Constitution of the Republic of Indonesia, is a form of mechanism.check and balanceswhich is not functional but issupreme. To maximize objectivity regarding the quality of constitutional judges, tiered selection through a mechanismcheck and balancesBased on the function of the institution that carries out the functions of state power, this is an option. This option is one of the efforts to strengthen the independence of the Constitutional Court. To realize this idea, it is necessary to make a fifth amendment to the 1945 Constitution of the Republic of Indonesia, specifically by reconstructing Article 24C paragraph (3) of the 1945 Constitution of the Republic of Indonesia.